The Influence of Artificial Intelligence (AI) Capability on Organizational Performance Mediated by Process Automation, Cognitive Insight, Cognitive Engagement and Organizational Creativity: Study of Startup Companies in Solo Raya - Febytama, Rerynda Dita; Suyono, Joko (International Journal of Science and Society, 2025)
Grounded in Resource-Based Theory (RBT), this study investigates the influence of artificial intelligence capabilities on organizational performance, with automation processes, cognitive insights, cognitive engagement, and organizational creativity acting as mediating mechanisms. This study uses a survey method. The research population is employees in each division of artificial intelligence (AI) users at start-up companies in Solo Raya. Purposive sampling was employed, yielding 250 returned questionnaires. The data were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that: (1) artificial intelligence capabilities do not have a statistically significant direct impact on organizational performance; and (2) artificial intelligence capabilities exert a significant positive influence on process automation; (3) process automation does not significantly influence organizational performance; (4) process automation does not serve as a mediating mechanism in the relationship between artificial intelligence capabilities and organizational performance; (5) artificial intelligence capabilities have a significant effect on cognitive insights; (6) cognitive insights do not exert a significant influence on organizational performance; (7) cognitive insights do not mediate the relationship between artificial intelligence capabilities and organizational performance; and (8) artificial intelligence capabilities significantly influence cognitive engagement; (9) cognitive engagement does not significantly influence organizational performance; (10) cognitive engagement does not mediate the relationship between artificial intelligence capabilities and organizational performance; (11) artificial intelligence capabilities exert a significant influence on organizational creativity; (12) organizational creativity has a significant positive impact on organizational performance; and (13) organizational creativity serves as a mediating mechanism in the relationship between artificial intelligence capabilities and organizational performance.